Operational response: Policing persons with mental illness in Australia - Miles-Johnson, Toby (Journal of criminology, 2022)
Across the globe, policing persons with mental illness (PWMI) in crisis involves significant police work. Police must respond effectively to individuals whose behaviour and language are often erratic, and who may be intoxicated or experiencing psychosis. In Australia, police are often criticised for inappropriately handling mental health crises in the community and for differentially policing PWMI in crisis. To better understand Australian police response to PWMI in crisis, this study conducted interviews with 25 operational police officers working in one of the largest Australian state police organisations. The findings indicate that police response to PWMI in crisis is underpinned by trial-and-error practices, because officers are insufficiently trained to manage PWMI in crisis, and police are resistant to accept tasks considered ?welfare work?. Officers are also relieved when response to PWMI in crisis includes mental health practitioners. We argue that whilst the availability of interagency schemes in Australia is generally restricted to metropolitan areas, effective policing response to PWMI in crisis should include a collaborative response between police and mental health practitioners.